2006
DOI: 10.1002/path.1952
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin D3 expression in primary Ta/T1 bladder cancer

Abstract: Cyclin D3 deregulation has recently been reported in bladder cancer but its prognostic significance remains uncertain. A cohort of 159 patients with stage Ta or T1 primary bladder tumours was investigated to determine the significance of cyclin D3 expression in association with other G1-S phase regulators of the cell cycle (p53, p21Waf1, p27kip1, cyclin D1), including tumour proliferation (ki67-MIB1); its association with conventional clinicopathological parameters; and the relationship between cyclin D3 and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
16
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 41 publications
(65 reference statements)
2
16
0
1
Order By: Relevance
“…We found up-regulation of Cyclin D3 gene to be present in about one third of secondary CIS cases. This result agrees with our previous work showing Cyclin D3 protein upregulation in high-grade bladder carcinoma [24,25,27]. In addition, we have observed that none of primary CIS cases entering the current study had Cyclin D3 gene amplification, raising the question if the known differences in aggressiveness between primary and secondary CIS cases could be explained by differences in genetic alterations between these two forms of bladder CIS; this could be related to a higher cell-cycle regulatory genes alteration in secondary CIS.…”
Section: Discussionsupporting
confidence: 95%
See 4 more Smart Citations
“…We found up-regulation of Cyclin D3 gene to be present in about one third of secondary CIS cases. This result agrees with our previous work showing Cyclin D3 protein upregulation in high-grade bladder carcinoma [24,25,27]. In addition, we have observed that none of primary CIS cases entering the current study had Cyclin D3 gene amplification, raising the question if the known differences in aggressiveness between primary and secondary CIS cases could be explained by differences in genetic alterations between these two forms of bladder CIS; this could be related to a higher cell-cycle regulatory genes alteration in secondary CIS.…”
Section: Discussionsupporting
confidence: 95%
“…Our finding of a strong association of Cyclin D3 gene amplification with recurrence-free and mainly with progression-free survival could indicate that there is an important deregulation of Cyclin D3 gene and protein over-expression in high-grade bladder cancer [24,25,27]. Moreover, it seems that Cyclin D3 alteration is a potentially relevant finding since the use of cell-cycle regulatory proteins as therapeutic targets of their modulators, represents an active field of research [24]. Available modulators of Cyclin D3 expression such Interferon-α and flavopiridol, that can induce cell-cycle arrest by directly inhibiting cyclin dependent kinases and by downregulation of Cyclin D3, might represent a future alternative to other conventional therapeutic approaches in a subset of bladder CIS patients at higher risk of aggressive behavior.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations